A Paper World: The Album Amicorum as a Collection Space - Keblusek, Marika (Early Modern Low Countries, 2022)
This essay examines early modern alba amicorum as collections of social and intellectual networks, personal memories, and other textual and visual materials. In what way are these ‘paper worlds’ related to collections of objects, and to networks of connections? How do they interact with other book and manuscript genres, such as the emblem and the costume book? Taking the album of the Dutch collector Bernardus Paludanus (1550-1633) as a case study, an argument will be made regarding the conceptual and material kinship of alba with other forms of manuscript and print collections. The intermediality and materiality of friendship books will be shown to be crucial aspects for understanding how this medium functioned within early modern cultures of collecting and the communal production of memory and knowledge.